KEBIJAKAN DIVIDEN DAN VOLATILITAS HARGA SAHAM DI BURSA EFEK INDONESIA - Sutandijo Sutandijo (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
This study objective is to explore the impact of dividend policy (that are dividend payout ratio and dividend yield) on the investment risks reflected by the stock price volatility for the Indonesia capital market (IDX). Following to the study of Baskin (1989), the multiple least squares regression model is used in this paper. Also, following Baskin (1989), other four independent variables namely firm size, asset growth, leverage and earnings volatility added to the model. The sample of data is comprised of 64 public firms in the Kompas100 Index for 5 consecutive years from 2012 to 2016 of which are listed on the Indonesia Stock Exchange (IDX). The results indicate that the dividend yield and the dividend payout ratio do not have significant influence to the stock price volatility In addition, firm size is negatively related to the stock price volatility and it has a statistically significant relationship. The result also indicate earnings volatility positively has influence to the stock price volatility. But, as for leverage and asset growth the results are not statistically significant. As for a conclusion, the dividend policy of the firms listed in Indonesia Stock Exchange (IDX) is not effective to influence the stocks’ risks or affect investors’ investment decisions. It seems that that firms needs a more stable and consistent dividend policy to effectively influence the stock price volatility in Indonesia Stock Exchange (IDX)